JMASM 46: Algorithm for comparison of robust regression methods in multiple linear regression by weighting least Square Regression - Mohd Ibrahim, Mohamad Shafiq; Wan Ahmad, Wan Muhamad Amir; Zafakali, Nur Syabiha (2017)
The aim of this study is to compare different robust regression methods in three main models of multiple linear regression and weighting multiple linear regression. An algorithm for weighting multiple linear regression by standard deviation and variance for combining different robust method is given in SAS along with an application.